Christmas vs. the Walters [videorecording (DVD)] - D'Amato, Peter A.; D'Amato, Peter A.; D'Amato, Peter A.; Smith, Shawnee; Smith, Shawnee; Winters, Dean, 1964-; Aaron, Caroline (MVD Visual, 2021)
Follows an over-burdened mother with a loving but dysfunctional family as she tries to create a perfect Christmas.